Religion and Psychological Values in Culinary Tradition Within Local Communities of West Kalimantan - Hariansyah Hariansyah; Ana Rosilawati (Al-Albab, 2021)
The article aims to explore culinary tradition that penetrates the public space which does not give room for tolerance because it has to deal with the rules of Islamic law. Food is perceived as being in a binary opposition: having an integration effect or being a social conflict resolution. Food is presented to the public space as a duplication of scriptural sources, a marker of tradition, an ecological balancing argument, and an indication of social shift. This paper confirms that dining tradition is proven to have an Islamic ideology. It is indicated by the ijab qabul phenomenon that accompanies the culinary tradition procession as an entity enriching the concept of fiqh among people living in coastal areas regarding the concept of food. In addition, eating and its traditions have an effect on environmental conflict resolution in the coastal areas of West Kalimantan. The traditions of food, land, houses, gatherings and reciting prayers for safety are all important ethnic characteristics in West Kalimantan. These five entities, which are perceived by the people of Kalimantan as provisions for life, have proven to be of no subjective values; they are reserved only for anyone with productive land. However, farm products in the form of food are also distributed to anyone in need. When someone has fulfilled the ber-saro'an (the invitation to eat; berontang or saprahan) in a village, they are no longer treated as “strangers”. This tradition is not only about eating but also has to do with the emergence of variants of Islamic fiqh in the coastal areas indicating psychological values.